Place Attachment in Foreign Psychology: Theoretical Approaches and Empirical Research - O.R. Tuhina (Современная зарубежная психология)
The article provides an overview of studies of the phenomenon of attachment to place of residence in foreign studies. A comparison of the points of view of foreign researchers on the relationship between the categories “Place Attachment” and “place identity” is carried out. Empirical studies of attachment to place of residence as a factor influencing intergroup relations and environmental behavior of residents in different sociocultural conditions are analyzed. It has been revealed that attachment to place of residence, according to the results of modern research, is a significant factor influencing intergroup relations, however, the characteristics of the influence are determined by the sociocultural context. The results of the analysis showed that the influence of place attachment largely determines pro-environmental behavior in relation to a place that is significant for a person. The article also analyzes the results of empirical studies of predictors of attachment to the place of residence: socio-demographic, socio-psychological, as well as the perception and assessment of the characteristics of the place of residence. It was revealed that, despite a large number of studies on the correlates and predictors of attachment to a place, today there are no scientific theories that explain the psychological mechanisms of a person’s connection with his place of residence.